2022
DOI: 10.1016/j.envres.2021.112638
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 circulation in Croatian wastewaters and the absence of SARS-CoV-2 in bivalve molluscan shellfish

Abstract: The circulation of SARS-CoV-2 in the environment has been confirmed numerous times, whilst research on the bioaccumulation in bivalve molluscan shellfish (BMS) has been rather scarce. The present study aimed to fulfil the knowledge gap on SARS-CoV-2 circulation in wastewaters and surface waters in this region and to extend the current knowledge on potential presence of SARS-CoV-2 contamination in BMS. The study included 13 archive wastewater and surface water samples from the start of epidemic and 17 influents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 46 publications
(65 reference statements)
1
8
0
Order By: Relevance
“…The prevalence of infection ranged from 0.05 to 0.38%, showing a positive correlation with clinical observations. Other studies detected SARS-CoV-2 viral RNA in wastewater in India (Arora et al 2020 ), Germany (Westhaus et al 2021 ), the USA (Wu et al 2021 ; Barua et al 2022 ), Croatia (Brnić et al 2022 ), and the United Arab Emirates (Hasan et al 2021 ).…”
Section: Introductionmentioning
confidence: 98%
“…The prevalence of infection ranged from 0.05 to 0.38%, showing a positive correlation with clinical observations. Other studies detected SARS-CoV-2 viral RNA in wastewater in India (Arora et al 2020 ), Germany (Westhaus et al 2021 ), the USA (Wu et al 2021 ; Barua et al 2022 ), Croatia (Brnić et al 2022 ), and the United Arab Emirates (Hasan et al 2021 ).…”
Section: Introductionmentioning
confidence: 98%
“…Mengovirus, a murine picornavirus, was used as a process control for nucleic acid (NA) extraction. MgV or other non-enveloped viruses were used as process control for SARS-CoV-2 WBE by other teams previously ( Barril et al, 2021 ; Alamin et al, 2022 ; Brnić et al, 2022 ). Here it was considered adequate as our concentration step relies on ultracentrifugation, which is efficient on both enveloped and non-enveloped virions, and early tests showed similar efficiencies using a porcine coronavirus (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…Oysters and other bivalves are known as ‘filter feeders’ because they filter organic matter, including viruses and bacteria, present in seawater through their midgut gland and concentrate them in their bodies ( Brnić et al, 2022 ; Desdouits et al, 2021 ; Le Guernic et al, 2022 ; Mancusi et al, 2022 ; Polo et al, 2021 ). Previous studies have elucidated a marked infection cycle that arises when norovirus from the feces of infected people seeps into the aquatic environment through sewage and accumulates in the bodies of oysters and other bivalves cultivated in coastal areas.…”
Section: Introductionmentioning
confidence: 99%
“…The latter are consumed by humans without sufficient heating needed to kill the virus ( Brnić et al, 2022 ; Desdouits et al, 2021 ; Le Guernic et al, 2022 ). Although several studies have reported a low risk of SARS-CoV-2 transmission through food ( Bondad-Reantaso et al, 2020 ; Godoy et al, 2021 ), concern remains that a similar infection cycle may arise with SARS-CoV-2, although no details of such a cycle are yet known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation